2019
DOI: 10.3390/molecules24244490
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Saccharomyces and non-Saccharomyces Yeasts in the Formation of Pyranoanthocyanins and Polymeric Pigments during Red Wine Making

Abstract: Yeast are able to modulate many sensory parameters of wines during red must fermentation. The effect on color and on the formation of derived pigments during fermentation has been studied thoroughly since the 90s. Yeast can increase grape anthocyanin’s color by acidification by hyperchromic effect (increase of flavylium molecules). Recent studies with non-Saccharomyces species, as Lachancea thermotolerans, described the intense effect of some strains on anthocyanin’s color, and subsequent, stability, by strong… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 46 publications
(48 citation statements)
references
References 109 publications
1
47
0
Order By: Relevance
“…Other information related to the nature and bioavailability of anthocyanins, their properties and industrial applications as well as the formation of pyranoanthocyanins and polymeric pigments has been recently published in reviews [77][78][79][80].…”
Section: Non-saccharomyces-mediated Formation Of Stable Pyranoanthocymentioning
confidence: 99%
“…Other information related to the nature and bioavailability of anthocyanins, their properties and industrial applications as well as the formation of pyranoanthocyanins and polymeric pigments has been recently published in reviews [77][78][79][80].…”
Section: Non-saccharomyces-mediated Formation Of Stable Pyranoanthocymentioning
confidence: 99%
“…In addition to S. cerevisiae , grape must naturally contain mixed populations of other yeast genera and species, involved, to different extents, in alcoholic fermentation [ 3 ]. In spontaneous fermentation process, the initial phase is promoted by the action of a heterogeneous consortium of yeasts belonging to different non- Saccharomyces species usually characterised by a low fermentative power, while the final step was distinguished by dominance of S. cerevisiae strains [ 4 , 5 ]. In fact, the action of non- Saccharomyces is relevant (predominant) during the first stage of alcoholic fermentation until the alcohol level reaches 4% ( v / v ), when most non-Saccharomyces species can no longer survive [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Emerging evidence has demonstrated that the exclusive use of S. cerevisiae could result in a sensorial flattening of wines when compared with distinctive aromatic features of wines produced by spontaneous fermentation driven by the above-described yeast consortium [ 9 , 10 ]. Although the oenological potential of Saccharomyces strains has been deeply investigated, there is scarce information related to the impact of different non- Saccharomyces genera/species on the aromatic profile of wines [ 3 , 4 , 10 , 11 , 12 , 13 , 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Many reviews have studied different perspectives of non-Saccharomyces/S. non-cerevisiae yeasts for modern winemaking practices, including their influence on different wine quality parameters with an emphasis on traits such as the primary (or varietal) and secondary (or fermentative) aromas of wines, acidity, freshness, as well as specific styles of wines (such as traditional method sparkling wines and red table wines) [3,9,[15][16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%